PTU-321 Completing in-hospital alcohol detox in the community: is this safe practice?. (22nd June 2015) - Sidhu, PS; Lin, S; Tipton, A; Peagram, S; Karwa, R; Agrawal, A
Abstract : Introduction: The National Health Service expenditure on alcohol services is estimated to be £2.7 billion with over 78% of costs incurred from hospital-based care. Patients with alcohol problems are major contributors to hospital readmission. 1 Part contributor to this burden is the full in-hospital alcohol detox (AD) offered to such patients. We investigate the feasibility and safety of completing AD in the community. Method: Discharge summaries, case-notes and blood results were reviewed for patients initiating in-hospital AD between 1/10/2013 and 1/3/2014 and were followed up to 1/8/2014. Satisfying our in-hospital risk assessment criteria, specific patients were selected for community AD (CAD) completion. The criteria which would exclude a patient from CAD completion included complex withdrawals, symptomatic in the past 24 h, unsupported living, mental health instability, chaotic drug use, mixing alcohol and medications and neurological symptoms. Data was collected on demographics, Emergency Department (ED) re-attendance, re-admission to hospital, CAD days, community alcohol services (CAS) engagement and Maddrey's Discriminant Function (MDF). Results: 189 patients were identified requiring input from the in-hospital alcohol liaison team. Of these, 70% were male (n = 132) with mean age of 50 years old (range: 23 to 88 years). In-hospital AD was initiated in 76% (n = 144) of the patients and of these, 26% (n = 37) completed AD in the community satisfying the above criteria. Mean CAD completion days per patient was 3.3 days. There was no significant difference (SD) between full in-hospital AD and CAD completion in relation to subsequent ED re-attendance (p = 0.37), hospital re-admission and further AD (p = 0.97) and re-admissions secondary to alcohol (p = 0.98). Furthermore, there was no SD in readmissions of those referred to CAS (p = 0.24) or who had engaged with CAS (p = 0.87) between the groups. The severity of liver disease was similar as evidenced by a MDF score >32 in 8% in CAD completion and 11% of those whom completed AD in-hospital (p = 0.72). Conclusion: This study demonstrates that completing AD in the community using pre-selected criteria is feasible, safe and will reduce the NHS expenditure in this area. Additionally this data validates our criteria for early discharge although we recommend further confirmation of these findings in a larger cohort of patients across multiple sites. In addition, we also validate our current in-hospital risk assessment tool. Disclosure of interest: None Declared. Reference: Alcohol related disease: meeting the challenge of improved quality of care and better use of resources (2010). A joint position paper by BSG/BASL/AHA. www.bsg.co.uk